ANALYSIS OF BUSINESS STRATEGIES ON THE BOCAH JAJAN ANGKRINGAN (BOJAN) IN KOJA, NORTH JAKARTA - Setiawan, Elfa; Alwi, Mohammad Farhan (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2022)
This study was made based on observations for three months at Angkringan Bojan, the purpose of the observation was to find out the marketing strategies carried out by Angkringan Bojan to achieve its sales targets.                       From the observations, Angkringan Bojan has never reached the target set. This is because in the implementation of the Angkringan Bojan strategy, the SWOT (Strength, Weakness, Opportunity, Threat) analysis has not been carried out by comparing the strengths, weaknesses, opportunities, threats with existing theories.                       Angkringan Bojan needs to find a more strategic sales location than the previous location which is close to the market waste disposal. In its development, the author also recommends Angkringan Bojan to improve the quality, design, promotion and bonus of culinary products available on the menu, strengthen the security system with complex passwords and back up data to minimize the possibility of hackers.Key words: Marketing Strategy, Sales Target, SWOT Analysis, Culinary Products.